Investigation on indentation test of green sandstone under coupled effect of axial and confining stress - Fu, Ran; Yang, Weihao; Zou, Jiuqun; Huang, Xin (Frontiers in Earth Science, 2025)
To study the effect of confining stress on the indentation test of rock under different axial stress and the corresponding mechanism of penetrating rock fragmentation, physical and numerical experiments of single spherical button penetration into green sandstone under triaxial stress conditions were conducted. The results indicate that the indices of crushing load, yield, brittleness feature, and energy consumption first decrease and then increase with increasing confining pressure, under high axial pressure conditions (30 MPa) and the thickness of rock chips increases by 37%, from 1.11 mm to 1.52 mm. The opposite pattern is observed under low axial pressure conditions (15 MPa). The thickness decreases from 1.475 mm to 0.915 mm, with a reduction of about 50%. In general, under all confining stress conditions, specific energy under high axial pressure conditions is lower than that under low axial pressure conditions. The maximum difference reaches 285%. The numerical experiments suggest that the total number, direction and distribution of cracks show great consistency with experimental results of indentation tests. The smaller total number of cracks under high axial pressure conditions may be the main reason for the lower specific energy. This present study may provide some primary knowledge about the rock cracking character and breaking efficiency under different stress conditions. The analysis of micro-cracks provides an explanation for the patterns of rock fragmentation.